A Synthetic Model to Quantify Dissolved Organic Carbon Transport in the Changjiang River System: Model Structure and Spatiotemporal Patterns - Shucong Lv (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Riverine dissolved organic carbon (DOC) is an important carbon pool in the global biogeochemical cycle. DOC transport in river networks involves three processes: DOC input (including DOC release from terrestrial ecosystems and in situ production in river networks), in‐river removal, and export through watershed outlets or estuaries. DOC transport in large river networks is gaining attention due to its important role in carbon and nutrient supply and CO2 emission, for example. However, quantifying DOC input to rivers and in‐river removal is still not properly understood. This study developed a synthesis model to quantify DOC transport in the Changjiang River Network (CRN) by coupling spiraling theory with Strahler river order. Our study suggested that the wetlands proportion and soil organic matter are valid parameters in a DOC model and our simulations showed that approximately 2.65–4.86 Tg C/year entered rivers and 1.16–2.12 Tg C/year was exported to the estuary as DOC, with a removal proportion of over 50% throughout the CRN in 1980–2015. The subbasins of the Dongting Lake, the Yichang‐Jiujiang section of the mainstream, and the Min‐Tuo River were primary contributors of DOC load, accounting for approximately 45% of the bulk DOC load of the CRN. The subbasins of Jinsha River and Yalong River in the upper reaches of the CRN and the subbasin of Wu River contributed less than 10% of the DOC load. DOC export by the CRN accounted for 0.3–1.2% of the global DOC flux from land to sea.